Pengaruh Penggunaan Gadget terhadap Prestasi Belajar Peserta Didik di MA Darul Muttaqien Kumbara Utama - Nur Azizah, Khusnul (Lembaga Anotero Scientific, 2022)
A gadget is an item with various applications that can provide various news media, social networks, hobbies, and even entertainment. Learning achievement is the result or level of ability that students have achieved after following the teaching and learning process within a certain time, in the form of changes in behavior, skills and knowledge. Then it will be measured and quantified in numbers or statements. The aim of this research is to find out whether gadgets can influence student achievement at MA Darul Muttaqien. The research method used is a quantitative method. The sample was taken using a purposive sampling technique, namely 30 respondents. The instruments used in this research were questionnaires and observation sheets. The population of this study was 15% of students in classes X, XI and XII of MA Darul Muttaqien, and were taken randomly. The conclusion of this research is that there is a relationship between gadget use and the level of student learning achievement at MA Darul Muttaqien Kumbara Utama.